FAKTOR YANG TURUT BERPENGARUH TERHADAP KEJADIAN MALARIA DI KELURAHAN HAMADI DISTRIK JAYAPURA SELATAN - Mina Sipayung (STRADA : Jurnal Ilmiah Kesehatan, 2013)
Background: Malaria desease is still an problem which is important in Indonesian, in the regions which frequently visited by inhabitants new of regions non endemic frequent occurs extraordinary events , which raises many deaths. Regions Jawa, Bali grouped as regions hipoendemik namely Spleen Rate (SR <10%), whereas Sumatera, Kalimantan, NTT, Maluku, Papua categorized hyperendemik with SR> 50%. Anopheles Farauti is the main vector malaria in Papua can live in standing water associated with the land. Malaria attacks all age groups. Especially in the Puskesmas Hamadi, malaria ranks second in 2010. This is due to the geographical condition in kelurahan Hamadi, flat and marsh that supports a breeding ground for malaria vectors. This study aims to determine the factors that helped influence on the incidence of malaria in working area of Puskesmas Hamadi kelurahan Hamadi, Distrik Jayapura Selatan. Methods: This research was analytic observational, using case control approach. Sampling technique is purposive sampling. Population in this study were all permanent residents aged> 15 years, who live in the kelurahan Hamadi. Validity of the results proved positive malaria blood test at Puskesmas Hamadi. Variables examined included: the marsh, the ditch, and the quality of public attitudes to the type of research Case Control Study using analysis of simple and multiple logistic regression, Sample size is 81 people, comparison of case and control samples is 1:1 so the total sample of 162 people. Results:Based on multivariate analysis, risk factors obtained quality residential and community behavior were statistically significant, co-dominant effect on the incidence of malaria in kelurahan Hamadi Distrik Jayapura Selatan. As seen from based on bivariate and multivariate analysis, the variable quality of housing (p=0,001) effect on the incidence of malaria by CI 95% 0,222 <OR <1,083 and value OR = 3.1. Commuting variables significant (p=0,000) with CI 95%, 0,222 <OR <1,083 and value of OR=4.7. Conclusion: Quality residential and community behavior is a risk factor for the incidence of malaria in the Puskesmas Hamadi Distrik Jayapura Selatan, improve public knowledge about malaria is still low malaria control efforts.